Photochemical reactivity of zinc tetraphenylporphyrin induced by nonstoichiometric CdS nanoparticles in 2-propanol - Alex V. Isarov; John Chrysochoos (International Journal of Photoenergy)
The photoreactivity of zinc tetraphenylporphyrin (ZnTPP) in the presence of photoexcited CdS nanoparticles and molecular oxygen in 2-propanol has been revisited. The photodecomposition of ZnTPP in 2-propanol, in the presence of CdS(e-CB/h+VB) and molecular oxygen, is linked to isopropyl free radicals formed by both hole transfer from CdS(h+VB) to (CH3)2CHOH and the reaction of superoxide ion (O2−) with 2-propanol. Isopropyl free radicals react with ZnTPP, leading to the formation of ZnTPP•−. Intermediate paramagnetic species monitored by EPR spectroscopy (g=2.0029,ΔH=5.7G) were characterized as superoxides formed in the reaction of ZnTPP•− with O2. Further transformations of such EPR-active species lead to the formation of diamagnetic intermediate photoproducts of ZnTPP observed by absorption and emission spectroscopy.